Formosa Licensed Revolution and the Home Rule Movement, 1895-1945 - Kerr, George H. (University of Hawai'i Press, 2018)
Peking ceded Formosa to Japan in 1895, whereupon Japan became the first Asian power in modern times to possess a colony, and the island became a testing ground for imperial policies. For two centuries the formosan chinese had resisted authority imposed upon them by inefficient continental chinese. Now, tokyo extended to insular Formosa many reorganizing, modernizing measures characterizing japan's own vigourous Meijing Revolution. During the next fifty years, as living standards rose to approach those of japan proper, early leaderless Formosan resistance to alien rule developed into organized appeals for effective representation in local government and at tokyo. With reversion to continental chinese control at the end of world war II, Formosans expected to conserve and enhance gains made during the Japanese era. Bitter disappointment promptly led again to rebellious relations with the continent.The author, long resident in Formosa and exclusively concerned with Formosan affairs while in government service during and after World War II, is well qualified to comment upon Formosas history and prospects. He concludes that the japanese era left an ineradicable mark on the island people, an understanding of which will illuminate developments when peking in futre undertakes the formidable task of converting Formosa into a fully disciplined and integrated province of the People's Republic of China.